2023
DOI: 10.56061/fbujohs.1126000
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between the Perceived Stress Level and The Spousal Support on of the Women Who Have Miscarriages

Emel ÖNGAY,
Kerime Derya BEYDAĞ

Abstract: Bu araştırma, düşük yapan kadınların algıladıkları eş desteğinin kadınların algıladıkları stres düzeylerine etkisini belirlemek amacıyla yapılmıştır. Tanımlayıcı, kesitsel ve ilişki arayıcı nitelikteki çalışmanın evrenini, 1 Şubat-1 Mayıs 2019 tarihleri arasında İstanbul ili Anadolu yakasındaki bir doğum ve Çocuk Hastalıkları Hastanesine başvuran 182 kadın oluşturmuştur. Araştırma verileri, tanımlayıcı veri formu, Algılanan Stres Ölçeği (ASÖ) ve Eş Destek Ölçeği (EDÖ) ile elde edilmiştir. Kadınların ASÖ puan o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 9 publications
0
3
0
Order By: Relevance
“…Similarly, in the study by Yüksekal and Yurdakul (2021), the average SSS score of pregnant women was found to be 68.99 ± 10.8, indicating a high level of spousal support [25] . In Öngay's study (2019) on women who had miscarriages, the average SSS score was found to be 70.76 ± 11.44 [7] . In the study by Nazık et al (2010), pregnant women were found to perceive high levels of support from their partners [26] .…”
Section: Discussionmentioning
confidence: 95%
See 2 more Smart Citations
“…Similarly, in the study by Yüksekal and Yurdakul (2021), the average SSS score of pregnant women was found to be 68.99 ± 10.8, indicating a high level of spousal support [25] . In Öngay's study (2019) on women who had miscarriages, the average SSS score was found to be 70.76 ± 11.44 [7] . In the study by Nazık et al (2010), pregnant women were found to perceive high levels of support from their partners [26] .…”
Section: Discussionmentioning
confidence: 95%
“…The scale yields a minimum score of 27 and a maximum score of 81, with higher scores indicating greater perceived spousal support. The scale consists of four sub-dimensions: emotional support (1,2,3,4,6,9,12,16,21), material aid and information support (7,13,15,17,24,25,27), appreciation support (5,10,14,18,20,22,23,26), and social interest support (9, 11, 18) [16] . In this study, the Cronbach's alpha value of the scale was found to be 0.89.…”
Section: Spousal Support Scale (Sss)mentioning
confidence: 99%
See 1 more Smart Citation